Cytokine Candidate Genes Predict the Development of Secondary Lymphedema Following Breast Cancer Surgery - Leung, Geraldine (Mary Ann Liebert, Inc., 2014)
Background: Lymphedema (LE) is a frequent complication following breast cancer treatment. While progress is being made in the identification of phenotypic risk factors for the development of LE, little information is available on the molecular characterization of LE. The purpose of this study was to determine if variations in pro- and anti-inflammatory cytokine genes were associated with LE following breast cancer treatment. Methods and Results: Breast cancer patients completed a number of self-report questionnaires. LE was evaluated using bioimpedance spectroscopy. Genotyping was done using a custom genotyping array. No differences were found between patients with (n=155) and without LE (n=387) for the majority of the demographic and clinical characteristics. Patients with LE had a significantly higher body mass index, more advanced disease, and a higher number of lymph nodes removed. Genetic associations were identified for three genes (i.e., interleukin (IL4) 4 (rs2227284), IL 10 (rs1518111), and nuclear kappa factor beta 2 (NFKB2 (rs1056890)) associated with inflammatory responses. Conclusions: These genetic associations suggest a role for a number of pro- and anti-inflammatory genes in the development of LE following breast cancer treatment.